Identification of Fungus Causing Onychomycosis in Chicken Meat Traders in Traditional Markets - Mayumi, Ni Kadek Sintya; Habibah, Nur; Suyasa, I Nyoman Gede (JST (Jurnal Sains dan Teknologi), 2023)
Onychomycosis is an infection of the nails caused by dermatophyte, non-dermatophyte, and yeast. Infection is characterized by discoloration of the nails and thickening of the nail plate. The proliferation of fungi can occur in jobs that are often in direct contact with dirty, damp and wet work sites such as chicken meat traders. Because chicken traders make direct contact with chicken meat which causes the hands and nails of traders to become wet and moist. The purpose of this study was to identify the pathogenic fungi that cause onychomycosis on the fingernails of chicken meat traders at traditional market in Batubulan Village. Identification was carried out by the culture on Saboraoud Dextrose Agar (SDA) media and followed by microscopic examination of the growing fungal colonies with Lactophenol Cotton Blue staining. The results of this examination were that all samples were grown on Saboraud Dextrose Agar (SDA) media. The dermatophyte group was identified as many as 17 and the Yeast group was identified as many as 14. Most of the fungi identified on the fingernails of chicken butchers were non-dermatophytes, 22 of which were Aspergillus sp.